Penurunan Bilangan Peroksida Dan Asam Lemak Bebas Pada Minyak Jelantah Menggunakan Serbuk Mahkota Dewa - Mutiara Putri Utami Susanto; Kenny Kencanawati; Dwi Tia Septiani; Sani Nurahayu (Sainteks: Jurnal Sain dan Teknik, 2020)
The study used mahkota dewa as adsorben to decrease of the peroxide number and free fatty acids on the used cooking oil with immersion variations for 2 days dan 3 days and also concentration variations of mahkota dewa 5 % w/v, 10 % w/v, and 20 % w/v. The results of the peroxide analysis test still exceed the required number of SNI namely 10 meq O2/kg and the results of the free fatty acid analysis test in the sample with immersion and stirring time for 2 days and 3 days the concentration of mahkota dewa 20 % w/v has met the SNI, which is 1.04 % and 0.91%.